(untitled) (Scientific journal of the Fergana State University, 2024)
This article is about the long-term production carried out in Yozyovon and Tashlogi of Fergana region, which supports the production technologies of grain, cotton and livestock products. The research will help to study the ways of crop rotation and efficient potato cultivation in the agrocenosis of growing vegetables, pulse crops, and medicinal plants. In the study, consideration of such issues as loading from intensive technology in barley production, norm of mineral fertilizers and source of soil agrochemical. The quantity and production effect of mineral fertilizers for barley cultivation in the soils of Fergana region, at the same time, were analyzed in terms of places and practical work processes in crop rotation. It is useful for the production of optimal agrotechnological products to support with the best mineral fertilizers in the cultivation of sugar barley.